The Influence of Digital Marketing Capability and Talent Development on Business Performance: The Mediating Role of Innovation Capability among Creative Industry Micro, Small, and Medium Enterprises (MSMEs) in Garut Regency, Indonesia - Ahmad Rojikun; Agustinus Yanuar Budhi Heriyanto (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study investigates the influence of Digital Marketing Capability and Talent Development on Business Performance, with Innovation Capability as a mediating variable among creative-industry Micro, Small, and Medium Enterprises (MSMEs) in Garut Regency, Indonesia. A quantitative approach was employed using a structured questionnaire distributed to MSME owners and managers. Of the 120 questionnaires distributed, 100 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results reveal that Digital Marketing Capability and Talent Development have positive and significant effects on Innovation Capability. However, Digital Marketing Capability, Talent Development, and Innovation Capability do not significantly influence Business Performance. Furthermore, Innovation Capability does not mediate the relationships between Digital Marketing Capability, Talent Development, and Business Performance. These findings suggest that strengthening digital capability and human resource development alone is insufficient to improve business performance without complementary organizational and environmental factors. This study contributes to the Resource-Based View and Dynamic Capability Theory by highlighting the importance of innovation capability development while emphasizing the need for integrated strategies to achieve sustainable business performance among creative-industry MSMEs.